EFL students’ perceptions of blended learning in English language course: learning experience and engagement - Nurmala Elmin Simbolon (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2021)
The importance of blended learning has been emphasised during the current restriction caused by the coronavirus diseases 2019 (COVID-19). But there is a scarcity of studies on students’ learning experience in blended learning, particularly using WhatsApp as one of the learning tools. A combination of classroom meetings and online learning is implemented in a vocational university in Indonesia. The research reported in this article aims to examine students’ perceptions of their learning experience in a blended method of learning incorporating social media WhatsApp and Google Classroom application as learning instruments. The dataset includes a questionnaire consisting of a four-point Likert scale and open-ended questions, a recording of WhatsApp chat history, and students' work in Google Classroom. Data analysis uses a multi-methods approach. Descriptive analysis is used for the closed-ended questions using the Excel program and content analysis for the open-ended questions. Results show that students positively perceive their learning experience in blended learning. Students also articulate their concerns of the internet connection and instruction clarity on the online learning materials. This paper highlights some implications of the research findings including the lecturer's need for professional development that may enable them to help students succeed in blended learning.